Study the Performance of Low Cost Material (Peanut Hulls) for Dye Adsorption Using Inverse Fluidized Bed - Saber Majeed, Najwa; Abood Alwan, Shaimaa (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The present study dealt with the removal of methylene blue from wastewater by using peanut hulls (PNH) as adsorbent. Two modes of operation were used in the present work, batch mode and inverse fluidized bed mode. In batch experiment, the effect of peanut hulls doses 2, 4, 8, 12 and 16 g, with constant initial pH =5.6, concentration 20 mg/L and particle size 2-3.35 mm were studied. The results showed that the percent removal of methylene blue increased with the increase of peanut hulls dose. Batch kinetics experiments showed that equilibrium time was about 3 hours, isotherm models (Langmuir and Freundlich) were used to correlate these results. The results showed that the (Freundlich) model gave the best fitting for adsorption capacity. Different size ranges of peanut hulls (PNH) were fluidized by a downward flow of an methylene blue dye dissolved in water in an inverse fluidization mode. In the inverse fluidized bed experiments, the hydrodynamics characteristics, the effect of initial methylene blue concentration Co 5, 10 and 20 mg/L, particle size 1.18-2, 2-3.35 and 3.35-4 mm, mass of adsorbent 25, 60 and 80 g, superficial fluid velocity 0.016, 0.019 and 0.027 m/s and effect of chemical modification were studied. The optimum conditions of adsorption in inverse fluidized bed were initial concentration was 5 mg/L, particle size was 1.18-2 mm size, mass of PNH is 80 g and superficial fluid velocity was 0.019 m/s. Also the adsorption capacity of PNH increased after modification by Nitric acid. UV-Spectrophotometer was used to determine the methylene blue concentration.